Targeting intracellular pathways in idiopathic inflammatory myopathies: A narrative review - La Rocca, Gaetano; Ferro, Francesco; Baldini, Chiara; Libra, Alessandro; Sambataro, Domenico; Colaci, Michele; Malatino, Lorenzo; Palmucci, Stefano; Vancheri, Carlo; Sambataro, Gianluca (Frontiers in Medicine, 2023)
In recent decades, several pieces of evidence have drawn greater attention to the topic of innate immunity, in particular, interferon (IFN) and Interleukin 6 in the pathogenesis of idiopathic inflammatory myopathies (IIM). Both of these molecules transduce their signal through a receptor coupled with Janus kinases (JAK)/signal transducer and activator of transcription proteins (STAT). In this review, we discuss the role of the JAK/STAT pathway in IIM, evaluate a possible therapeutic role for JAK inhibitors in this group of diseases, focusing on those with the strongest IFN signature (dermatomyositis and antisynthetase syndrome).